Supporting cooperative caching in mobile ad hoc networks using clusters. (7th December 2006) - Chand, Narottam; Joshi, R.C.; Misra, Manoj
A novel scheme, called Cluster Cooperative (CC), for caching in mobile ad hoc networks is presented. In CC, the network topology is partitioned into non-overlapping clusters based on the physical network proximity. In each cluster, a 'super' node called Cache State Node (CSN) is chosen to maintain the Cluster Cache State (CCS). For a data miss in the local cache, each client searches the data with its CSN before the request is forwarded to the next client that lies along routing path towards source. Simulation experiments show that CC achieves significant improvements in comparison with other caching strategies.